Material classification and composite elastic modulus of hybrid PVA fiber ferrocement - Abushawashi, N.; Vimonsatit, Vanissorn (American Society of Civil Engineers (ASCE), 2016)
Strain-hardening material properties of cementitious composites have been achieved by the hybridization of fibers in the matrix. The modulus of elasticity of thin ferrocement composites depends on the elastic modulus of the cement mortar and some factors pertaining to the difference in the elastic modulus of the mesh and mortar. This study presents an experimental and analytical investigation aimed at determining the modulus of elasticity of hybrid polyvinyl alcohol (PVA) ferrocement (HFF). The study had two stages: the first was to determine the elastic modulus of hybrid fiber cementitious (HFC) composites, and the second was to determine the elastic modulus of HFF panels based on flexural tests. An analytical calculation was conducted using the data obtained from a standard compression test, nanoindentation test, and finite element (FE) analysis. The nanoindentation of a representative volume element (RVE) and the transversely isotropic material behavior using FE modeling of an RVE were compared and evaluated. The calculated composite elastic modulus is in good agreement with the elastic modulus obtained from the flexural tests and the FE-model.